2017
DOI: 10.1101/205310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bipolar oscillations between positive and negative mood states in a computational model of Basal Ganglia

Abstract: Bipolar disorder is characterized by mood swings -oscillations between manic and depressive states. The swings (oscillations) mark the length of an episode in a patient's mood cycle (period), and can vary from hours to years. The proposed modeling study uses decision making framework to investigate the role of basal ganglia network in generating bipolar oscillations. In this model, the basal ganglia system performs a two-arm bandit task in which one of the arms leads to a positive outcome, while the other lead… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…Reinforcement learning models suggest healthy human choices ideally tend to maximize long-term beneficial outcomes (Balasubramani, Chakravarthy, Ali, et al, 2015a; Balasubramani et al, 2014; Balasubramani, Moreno-Bote, et al, 2018; Balasubramani & Chakravarthy, 2019; A. Gupta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reinforcement learning models suggest healthy human choices ideally tend to maximize long-term beneficial outcomes (Balasubramani, Chakravarthy, Ali, et al, 2015a; Balasubramani et al, 2014; Balasubramani, Moreno-Bote, et al, 2018; Balasubramani & Chakravarthy, 2019; A. Gupta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Translational neuroscience studies show that reward based decision processing deficits are found in depression and in attention disorders, leading to difficulty in reward integration and foresighted choice-behaviors (Balasubramani, Chakravarthy, Ali, et al, 2015b; Balasubramani & Chakravarthy, 2019; Gradin et al, 2011; Groen et al, 2013; Miller & Seligman, 1973; Silvetti et al, 2013; Ziegler et al, 2016). Such individuals then focus on the immediate reward outcome in the short-term, characterized by a prolonged attenuation of temporal discounting of rewards (Eshel & Roiser, 2010; Pizzagalli et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parkinson's disease (PD) is a neurodegenetative disorder resulting from a loss of dopaminergic neurons, which leads to alterations of neural activity in the basal ganglia (BG), thalamus (TH), and cortex [1][2][3]. The BG is the main pathologic area of PD, which is known to be implicated in choice selection, timing, working memory, and motor sequencing [4][5][6]. Parkinsonian tremor is a well-recognized cardinal symptom affecting~70% of PD patients, which is primarily a rest tremor with the frequency in 3-9 Hz range.…”
Section: Introductionmentioning
confidence: 99%